Educational leaders encouraging the intellectual and professional capacity of others : a social justice agenda - Murakam, Elizabeth; Pankake, Anita M., 1947- (Educational leadership for social justice., 2012)
This book examines how to encourage the development of others towards social justice practices. The processes of development include practices such as mentoring, coaching, professional development, and the exploration of alternatives to reculture the work environment and enhance collaborative partnerships. Many groups play a role in the leadership and improvement of social justice opportunities in education, such as students, new teachers, veteran teachers, teacher leaders, new campus leaders, veteran campus leaders, parents, district leaders, non-certified school personnel and board of education members. Their preparation and development are explored in this volume through the people's voices and experiences. Finally, challenges can be recognized in the effort to encourage the development of others, including local and federal policies, new forms of academic delivery, and the preparation of leaders in ever-evolving educational structures. These issues will be fully explored with the aim of informing practitioners and scholars in the field of educational leadership.